Metabolic rate of Cherax quadricarinatus - Ludi Parwadani Aji (Faculty of Mathtmatics and Natural Sciences, 2012)
Temperature is the most prominent factor that influence metabolic rate of aquatic animals. In general, the increasing temperature of 10 degrees Celsius will improve metabolic rate two-fold. Therefore, this research aim is to examine the metabolic rate and Q10 value of crayfish. The metabolic rate of crayfish (Cherax quadricarinatus) was examined by determining oxygen consumption rates using caulorimetric respirometer. The oxygen consumption rates of Cherax quadricarinatus which acclimated at 23_C and 31_C is at around 0.52 and 0.7 uL/g/min respectively. Furthermore, the Q10 value of crayfish between 23_C and 31_C is 1.47. The oxygen consumption and Q10 value of crayfish is different compare with other aquatic invertebrate and ectotherms.